Formative (self-)assessment as autonomous language learning - Cooker, Lucy (2012)
While learner autonomy is often lauded as an important goal in language education, applied linguists have debated if it is a construct that has been given proper attention in terms of definition and assessment. In order to address this debate the researcher implemented a two-phase study within the context of higher education. Theories of learner autonomy, sustainable assessment and transformative learning guided the study design. In the research design, the nexus between language learner autonomy and assessment as learning was first explored in phase one of the study. Here survey methodology was used on a global scale: Findings from 45 respondents in 13 countries indicate that indeed language learner autonomy is being widely assessed, and, further that a variety of tools, evidence and people are implemented in this task. In phase two of the study, the most important stakeholders of learner autonomy - language learners - participated in Q-methodological study of their perceptions of the non-linguistic outcomes of learning in an autonomous environment: A total of 30 participants from Hong Kong, Japan and the UK completed a Q sort and interview. The findings of the Q study showed that there were six different ways of being autonomous, and these were interpreted as 'modes of autonomy'. These modes of autonomy were lastly used to devise a tool for the formative self-assessment of learner autonomy.